2013
DOI: 10.1371/journal.pone.0081315
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Food-Isolated Salmonella Strains through Pulsed Field Gel Electrophoresis (PFGE) and Enterobacterial Repetitive Intergenic Consensus (ERIC-PCR)

Abstract: All over the world, the incidence of Salmonella spp contamination on different food sources like broilers, clams and cow milk has increased rapidly in recent years. The multifaceted properties of Salomnella serovars allow the microorganism to grow and multiply in various food matrices, even under adverse conditions. Therefore, methods are needed to detect and trace this pathogen along the entire food supply network. In the present work, PFGE and ERIC-PCR were used to subtype 45 Salmonella isolates belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 32 publications
(36 reference statements)
5
30
2
3
Order By: Relevance
“…ERIC-PCR has been shown as a powerful tool for demonstrating variability among isolates (Sachdeva & Virdi, 2004;Fendri et al, 2013). It has been suggested that ERIC sequences would in all likelihood have some functional role in the bacterial cell (Asinmov et al, 2005;De Gregorio et al, 2005) although this has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ERIC-PCR has been shown as a powerful tool for demonstrating variability among isolates (Sachdeva & Virdi, 2004;Fendri et al, 2013). It has been suggested that ERIC sequences would in all likelihood have some functional role in the bacterial cell (Asinmov et al, 2005;De Gregorio et al, 2005) although this has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Only DNA samples which showed quality parameters of approximately two were used in this study. Fendri et al (2013) with the modifications described below. Each PCR reaction was made up of 1x DreamTaq TM Green Buffer with MgCl 2 (Thermo Fisher Scientific Inc., Asheville, NC, USA -EP0711), 1.0 pmol of primers ERIC1R (5′-ATG TAA GCT CCT GGG GAT TCA C-3′) and ERIC2 (5′-AAG TAA GTG ACT GGG GTG AGC G-3′) (Sigma-Aldrich, Saint Louis, MO, USA), 5 mM of MgCl 2 (Invitrogen Corp., Carlsbad, CA, USA), 240 µM of each deoxynucleotide triphosphate (dNTP) (Invitrogen Corp.), 5 µl of DNA template (approximately 60 ng), 2 U of Taq DNA polymerase (Thermo Fisher Scientific Inc.) and ultrapure water (Sigma-Aldrich) to a final volume of 25 µl.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, multilocus enzyme electrophoresis and multilocus sequence typing have been explored to link serotypes with housekeeping gene patterns (18)(19)(20), but neither method agreed well with results obtained by the traditional serotyping method. The bacterial identification method using whole-genome restriction patterns, pulsed-field gel electrophoresis, has been applied to some common serovars of Salmonella but could not achieve the quality of serotyping data because of variable patterns, even among strains with the same serovars (21). Lastly, MS techniques, especially matrix-assisted laser desorption ionization-time of flight MS, have been used to type Salmonella in recent years because of their speed and ease of use (22,23).…”
mentioning
confidence: 99%